Erlotinib treatment induces cytochrome P450 3A activity in non‐small cell lung cancer patients - Svedberg, Anna (Br J Clin Pharmacol, 2019)
AIMS: Erlotinib is a tyrosine kinase inhibitor used in the treatment of non‐small cell lung cancer highly metabolized by the cytochrome P450 (CYP) 3A. Hence, CYP3A4 activity might be a useful predictor of erlotinib pharmacokinetics in personalized medicine. The effect of erlotinib on CYP3A activity was therefore studied in non‐small cell lung cancer patients. METHODS: The study included 32 patients scheduled for erlotinib monotherapy. CYP3A activity was assessed using quinine as a probe before and during erlotinib treatment. Plasma from blood samples drawn 16 hours post quinine administration were analysed using HPLC with fluorescence detection to determine the quinine/3‐OH‐quinine ratio. RESULTS: Matched samples, available from 13 patients, showed an induction of CYP3A activity (P = 0.003, Wilcoxon's signed rank test) after 2 months of treatment. The quinine/3‐OH‐quinine ratio decreased from 20.2 (± 13.4) at baseline to 11.0 (± 4.34). Single‐point samples, available from 19 patients, supported the decrease in ratio (P = 0.007, Mann–Whitney U‐test). Generally, females had a higher CYP3A activity both at baseline and after two months of treatment. Statistical analysis by gender also showed significant increase in CYP3A activity (males, n = 10, P = 0.001, and females, n = 22, P = 0.001). CONCLUSIONS: An induction of CYP3A activity was observed after 2 months of erlotinib treatment which was also seen when subdividing based on gender. It could be important to take this into consideration for patients co‐administering other CYP3A‐metabolizing drugs during erlotinib treatment and also makes it difficult to use baseline CYP3A activity to predict erlotinib pharmacokinetics.